2015
DOI: 10.1111/gcb.12875
|View full text |Cite
|
Sign up to set email alerts
|

A pan‐Arctic synthesis of CH4 and CO2 production from anoxic soil incubations

Abstract: Permafrost thaw can alter the soil environment through changes in soil moisture, frequently resulting in soil saturation, a shift to anaerobic decomposition, and changes in the plant community. These changes, along with thawing of previously frozen organic material, can alter the form and magnitude of greenhouse gas production from permafrost ecosystems. We synthesized existing methane (CH ) and carbon dioxide (CO ) production measurements from anaerobic incubations of boreal and tundra soils from the geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 83 publications
10
114
1
Order By: Relevance
“…Our incubation was fully aerobic, but its results are consistent with the conclusion that respiration in the form of CO 2 is likely to dominate the high-latitude C feedback, and that aerobic soils, and the conditions under which currently waterlogged soils may drain, deserve particular attention. In terms of absolute flux rates, Treat et al (2015) reported mean CO 2 rates of 47 (all mineral soils) and 101 (for 20-100 cm soils) µg C-CO 2 g C −1 day −1 from a pan-Arctic synthesis of anaerobic soil incubations, which is somewhat lower than our aerobic incubation results. Treat et al (2014) also found CO 2 and CH 4 emissions to be strongly correlated with temperature and moisture based on an incubation of Alaskan peats.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Our incubation was fully aerobic, but its results are consistent with the conclusion that respiration in the form of CO 2 is likely to dominate the high-latitude C feedback, and that aerobic soils, and the conditions under which currently waterlogged soils may drain, deserve particular attention. In terms of absolute flux rates, Treat et al (2015) reported mean CO 2 rates of 47 (all mineral soils) and 101 (for 20-100 cm soils) µg C-CO 2 g C −1 day −1 from a pan-Arctic synthesis of anaerobic soil incubations, which is somewhat lower than our aerobic incubation results. Treat et al (2014) also found CO 2 and CH 4 emissions to be strongly correlated with temperature and moisture based on an incubation of Alaskan peats.…”
Section: Discussioncontrasting
confidence: 80%
“…Methane was also a far smaller C flux than CO 2 from these soils, in particular at higher temperatures (as CO 2 was responsive to temperature, but CH 4 was not). This is true more generally: for example, Treat et al (2015) found a median CO 2 : CH 4 production ratio of 387 for anaerobic incu- bations of boreal soils. This is naturally far lower than our observed aerobic (and thus high-CO 2 ) ratios, but nonetheless consistent with them.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Wetlands serve as preferred grounds for Arctic herbivores such as snow geese (Gauthier et al, 1996;Massé et al, 2001;Doiron et al, 2014). They are also expected to produce more methane compared to shrub-dominated areas (Olefeldt et al, 2013;Nauta et al, 2015;Treat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%